(untitled) (Research, Society and Development, 2022)
The objective was to evaluate the prevalence and antimicrobial sensitivity profile of Klebsiella spp. and Staphylococcus spp. isolated from urine samples of women from a private Laboratory of Clinical Analysis in Conselheiro Lafaiete-MG, as well as the season of higher prevalence. A cross-sectional observational study of the quantitative type was conducted, aiming to collect secondary data on the prevalence and sensitivity profile of Klebsiella spp. and Staphylococcus spp. genera isolated from positive urine cultures in female patients aged 18 to 60 years, in the period from January to December 2019. During the study period, 41 positive urine cultures were identified in this laboratory from women within the stipulated age range, with the genus Klebsiella spp. being the most prevalent 13/41 (31.71%), followed by Staphylococcus spp. 11/41 (26.83%). From the results obtained in this study, it was possible to identify that all the objectives were achieved, since the number of cases of infections in female patients between 18 and 60 years of age was obtained, the season with the highest prevalence of urinary tract infection was evaluated, the pathogens of interest were presented in tables, and the sensitivity profile of bacteria to the main antimicrobials of clinical relevance was described.